Smart Office Application With IoT-Based Light Monitoring And Controlling Features - Achmad Hamdan; Bagus Aditama; Muladi Muladi; Wahyu Nur Hidayat (Lembaga Pengembangan Kinerja Dosen, 2024)
The activity of using office facilities such as turning on lights is usually carried out manually by human physical effort. Unbeknownst, this activity reduces the effectiveness of office users' performance and raises concerns about excessive electricity usage due to not knowing whether the lights are still on or have been turned off. Therefore, a smart office application based on the Internet of Things is needed to control the lighting conditions and monitor electricity usage. In this study, the device is developed using several sensors including Pzem-004T, RTC, LDR, and Firebase database. The research results in (1) light control can be done through an Android application utilizing the Firebase database divided into two modes: automatic and manual; (2) by utilizing serial communication from Esp32 with PZEM004T, the smartphone application can display real-time data and usage history to facilitate users in controlling and monitoring the lights; (3) light sensors (LDR) and Ultrasonic Sensors (HC_SR 04) function well to adjust the range of values as considerations for when the lights should turn on and off; (4) with PZEM004T-V3.0, the application can monitor energy usage, even up to the total cost of usage.